Well-care in Tondo’s Slums: Women-Driven Vocational Learning Knowledge Hubs Toward 2030’s Sustainable Development Goals - Fraizer, L. (INVOTEC, 2018)
Worldwide efforts—such as Sustainable Development Goals and its predecessor Millennium Development Goals—historically offers country policy makers, industry leaders, and proactive citizens an aspirational guiding charter for actions needed to address complex issues that our planet and its inhabitants are facing such as adversities related to poverty, employability, quality education and holistic health. Households who are fighting for mere subsistence often depend on its youngest to work and contribute to the family’s economic livelihood and survival. It is not uncommon, for instance, for some children from residential-industrial parts of Tondo to forego free compulsory primary school education in order to scour landfill for valuables that can be traded or sold for basic necessities such as food and water. Millions of impoverished others experience similar hardships around the world. As nationwide achievement is highly dependent upon the well-being of a thriving population—educational opportunities can be pragmatic for those who pursue it if basic needs can be met—holistic well-care for human and economic survival. Entrepreneurship cases are explored, specifically vocational life skills investments by female entrepreneurs which include digital literacy and basic well-being practices.